Chrysophanol is involved in the biofertilization and biocontrol activities of Trichoderma. (December 2016) - Liu, Shu-Ying; Liao, Chuan-Kai; Lo, Chaur-Tsuen; Yang, Hsueh-Hui; Lin, Kuo-Chih; Peng, Kou-Cheng
Abstract: The effect of chrysophanol, a secondary metabolite of Trichoderma harzianum, on the growth and disease resistance of cabbage against Botrytis cinerea was investigated. Chrysophanol assisted cabbage growth and promoted resistance against B . cinerea . Proteins related to photosynthesis were expressed in T . harzianum - and chrysophanol-treated cabbages. The transcription levels of photosynthesis- and sucrose transport-related genes increased in chrysophanol-treated cabbages. The transcription levels of chitinase increased in T . harzianum -treated cabbages and those of ascorbate peroxidase in T . harzianum - and chrysophanol-treated cabbages. Chrysophanol is involved in stimulating plant growth and photosynthesis and in eliciting host defense responses during the colonization of T . harzianum . Graphical abstract: Highlights: Chrysophanol stimulates plant growth. Chrysophanol stimulates CO2 fixation and phloem loading. Chrysophanol elicits host defence responses. Chrysophanol functions in Trichoderma as an elicitor.